Anti-Inflammatory Benefits of Antibiotics: Tylvalosin Induces Apoptosis of Porcine Neutrophils and Macrophages, Promotes Efferocytosis, and Inhibits Pro-Inflammatory CXCL-8, IL1α, and LTB4 Production, While Inducing the Release of Pro-Resolving Lipoxin A4 and Resolvin D1 - Moges, Ruth; De Lamache, Dimitri Desmonts; Sajedy, Saman; Renaux, Bernard S.; Hollenberg, Morley D.; Muench, Gregory; Abbott, Elizabeth M.; Buret, Andre G. (Frontiers in Veterinary Science, 2018)
Excessive accumulation of neutrophils and their uncontrolled death by necrosis at the site of inflammation exacerbates inflammatory responses and leads to self-amplifying tissue injury and loss of organ function, as exemplified in a variety of respiratory diseases. In homeostasis, neutrophils are inactivated by apoptosis, and non phlogistically removed by neighboring macrophages in a process known as efferocytosis, which promotes the resolution of inflammation. The present study assessed the potential anti-inflammatory and pro-resolution benefits of tylvalosin, a recently developed broad-spectrum veterinary macrolide derived from tylosin. Recent findings indicate that tylvalosin may modulate inflammation by suppressing NF-κB activation. Neutrophils and monocyte-derived macrophages were isolated from fresh blood samples obtained from 12- to 22-week-old pigs. Leukocytes exposed to vehicle or to tylvalosin (0.1, 1.0, or 10 µg/mL; 0.096–9.6 µM) were assessed at various time points for apoptosis, necrosis, efferocytosis, and changes in the production of cytokines and lipid mediators. The findings indicate that tylvalosin increases porcine neutrophil and macrophage apoptosis in a concentration- and time-dependent manner, without altering levels of necrosis or reactive oxygen species production. Importantly, tylvalosin increased the release of pro-resolving Lipoxin A4 (LXA4) and Resolvin D1 (RvD1) while inhibiting the production of pro-inflammatory Leukotriene B4 (LTB4) in Ca2+ ionophore-stimulated porcine neutrophils. Tylvalosin increased neutrophil phospholipase C activity, an enzyme involved in releasing arachidonic acid from membrane stores. Tylvalosin also inhibited pro-inflammatory chemokine (C–X–C motif) ligand 8 (CXCL-8, also known as Interleukin-8) and interleukin-1 alpha (IL-1α) protein secretion in bacterial lipopolysaccharide-stimulated macrophages. Together, these data illustrate that tylvalosin has potent immunomodulatory effects in porcine leukocytes in addition to its antimicrobial properties.